2018
DOI: 10.1123/jab.2017-0120
|View full text |Cite
|
Sign up to set email alerts
|

Center of Pressure and Perceived Stability in Basketball Shoes With Soft and Hard Midsoles

Abstract: This study aimed to investigate the effects of varying midsole hardness on center of pressure (COP) and perceived stability during basketball-specific tasks, as well as the correlation between COP and perception measurements. A total of 20 male basketball players performed 45° cutting and layup while wearing basketball shoes with soft and hard midsoles. COP trajectories were obtained from the Pedar insole system. Stability perceptions at the forefoot and rearfoot were assessed using 150-mm visual analogue scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…A previous study showed that basketball players are able to distinguish between shoe midsole hardness conditions through the perceptual parameter of comfort level while performing several basketball movements [10]. In another study on layup and side-cutting tasks, recreational basketball players indicated similar perceived stability for shoes with softer and harder midsoles, and that there was no relationship between biomechanical and subjective measurements [32]. In the present study, the majority of participants preferred playing on a wooden to an asphalt court.…”
Section: Perceptual Response To Playing Surfacescontrasting
confidence: 37%
“…A previous study showed that basketball players are able to distinguish between shoe midsole hardness conditions through the perceptual parameter of comfort level while performing several basketball movements [10]. In another study on layup and side-cutting tasks, recreational basketball players indicated similar perceived stability for shoes with softer and harder midsoles, and that there was no relationship between biomechanical and subjective measurements [32]. In the present study, the majority of participants preferred playing on a wooden to an asphalt court.…”
Section: Perceptual Response To Playing Surfacescontrasting
confidence: 37%
“…An additional question regarding stability of the footwear was also administered using the VAS (0 mm -extremely unstable, 100 mm -extremely stable). The VAS is a tool with high sensitivity and low bias tendency and has been previously used to assess the stability of footwear (Leong et al, 2018). The conventional shoes were shoes that are currently available on the market.…”
Section: Perceptions Of Footwearmentioning
confidence: 99%
“…Notably, the results of plantar pressure were inconsistent with the perceptual comfort of shoe L and shoe N in the above-mentioned plantar pressure and perceptual comfort scale tests [30]. Although shoe L has a lower plantar pressure on the forefoot, it is not as comfortable as shoe N. The results of plantar pressure indicated the advantage of the forefoot cushioning performance of shoe L. However, the midsole structure of shoe L should be improved to avoid excessive force concentration under intense impact from the pressure distribution.…”
Section: Comfort Perceptionmentioning
confidence: 74%